Avaliação neurocomportamental, mitocondrial e do envelhecimento após exposição a compostos orgânicos voláteis (COVs) em Caenorhabditis elegans - Soares, Marcell Valandro (2023)
Organic solvents are many used in industrial processes, among these solvents; we highlight the group benzene, toluene, ethylbenzene, and xylenes (BTEX), which are mainly emitted through industrial processes, but also by fossil fuel combustion. Exposures to these solvents occur mainly in two manners: intentional (drug abuse) or unintentional (environmental and occupational settings). In a context of abuse, the inhalation of toluene stands out, using glue shoes; whereas in non-intentional exposure, the contact occurs by BTEX mixture in the environment, and both exposures cause toxic effects to the organism, however, the specificity of the mechanisms involved is little explored. Based on this, our study sought to mimetize two exposure scenarios: using toluene, and simulating levels close to intentional use, and the BTEX mixture, simulating lower than occupational permissive levels, and investigating the long-term effects using the Caenorhabditis elegans model. The exposures were performed in a chamber by airborne methodology in a system applied to volatile compounds, and in the first scenario (intentional), we observed that exposure to toluene caused damage to dopaminergic neurons, locomotor and behavioral deficits associated with dopaminergic signaling, and also, using ex vivo/in vitro/in silico methodologies, it was seen that toluene possibly acts by inhibition of mitochondrial complex I, then, generates a mitochondrial dysfunction resulting in the outcome of neuronal death. In relation to the BTEX scenario, we observed that exposures to mixture, at permissive regulatory levels, generate an extensive deficit in nematode mobility, mitochondrial dysfunction, pigments accumulation and neuronal abnormalities, that together, using an only standardized index are correlated with loss of healthspan, as well as early aging. Together these findings, can established a possible new mechanism of toluene neurotoxicity, the mitochondrial dysfunction. And, furthermore, we reinforce the importance of investigation the role of mixtures, since regulatory levels are established only for the isolated agent, however, here it was observed that at permissive levels, the BTEX mixture generated long-term and irreversible effects.